Double-Edged Sword? The Impact of Online Misogyny on Female College Students’ Digital Activism in the Post-COVID-19 Era - Jo, Jung In (Violence against women, 2025)
Using original surveys to investigate how online gender-based harassment marginalizes or empowers female college students, we found increased exposure to misogyny polarizes digital participation. Women aware of gender inequality in Korea encountering online hate speech were more inclined to engage in online movements, unlike women who did not recognize such inequality. This highlights distinct opportunities in relation to digital activism, showing online hate speech can sometimes be a catalyst for online political participation. This study expands current research on digital protest, highlighting the political ramifications of empowering women in the critical context of their unequal democratic rights outside the West.